Comparison of Acidity, Reducing Sugars, Vitamin C, and Antioxidants of Several Types of Kombucha Tea: Review - Gunawan, Mutiara Sani; Kurniasih, Nunung (Fakultas Sains dan Teknologi UIN Sunan Gunung Djati Bandung, 2024)
Kombucha tea is a beverage produced from sweet tea using symbiotic bacteria and yeast. This study aims to investigate and compare the pH, carbohydrate reduction, vitamin C content, and antioxidant content of different varieties of kombucha, analysing the effect of fermentation time on chemical characteristics which include organoleptic tests (pH value, vitamin C content and reducing sugar) and antioxidant tests. Literature study on existing research is about the pH contained, antioxidant activity, vitamin C, and reducing sugar in several types of kombucha tea. It is expected that the results of this research will provide significant benefits in the food, health and other sectors with the potential to be a good option for individuals who want to consume high nutritional drinks and have antioxidant activity, as well as provide a pleasant taste experience. The research is expected to help fulfil people's nutritional needs and support the strength of the immune system.